2019
DOI: 10.21272/jes.2019.6(2).e1/
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of the Effect of Changing Tube Pitches on Heat and Flow Characteristics from Tube Bundles in Cross Flow

Abstract: Tube bundles are found in various heat transfer equipment for thermal energy transfer between fluids. However, the inter-spatial arrangement of the tubes of any tube bundle is a determining factor for its thermal and hydraulic performance. In this paper, the effect of varying the transverse and longitudinal pitches downstream staggered circular tube bundle on the heat transfer and flow characteristic was numerically analyzed. Seven variations of tube arrangements were studied by changing the tube pitches withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Lalot et al (1999) showed experimentally that a perforated plate with holes of equal diameter in the inlet header increased the heat transfer efficiency [10]. Recently, numerical studies have been conducted to increase the thermal performance of heat exchangers and air distribution devices by considering a perforated plate [11], baffles [12], or varying the transverse and longitudinal pitches of tube bundles [13].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lalot et al (1999) showed experimentally that a perforated plate with holes of equal diameter in the inlet header increased the heat transfer efficiency [10]. Recently, numerical studies have been conducted to increase the thermal performance of heat exchangers and air distribution devices by considering a perforated plate [11], baffles [12], or varying the transverse and longitudinal pitches of tube bundles [13].…”
Section: Introductionmentioning
confidence: 99%
“…Their numerical results generally showed that shell-and-tube heat exchangers with concave-cut baffles had a lower performance as compared with the single-segmental baffle type. In addition, they numerically studied the effect of tube pitch on heat and flow characteristics from tube bundles in crossflow conditions [13]. The tube bundles with decreasing pitches had higher heat transfer performance, whereas the low friction factor was obtained with increasing pitches, which also gave good thermal-hydraulic performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation